EVALUATION OF FINANCIAL PERFORMANCES OF SME’S LISTED IN THE BIST SME INDUSTRIAL INDEX BY USING TOPSIS MULTICRITERIA DECISION MAKING METHOD - Selcuk Kendirli; Muhammet Selcuk Kaya; Mustafa Bilgin (Journal of Economic Development, Environment and People, 2020)
In this study, the financial performances of SMEs listed in the BIST SME Industrial Index are evaluated by using TOPSIS multicriteria decision-making method. The data of the study acquired from annual financial statements that reported between the 2016-2018 period. Financial performance ranks of SMEs are determined for each year and thus comparative financial performances of SMEs are detected.